1990
DOI: 10.1542/peds.86.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Liver Transaminase Levels in Children With Blunt Abdominal Trauma: A Predictor of Liver Injury

Abstract: The medical records of 43 hemodynamically stable children with elevated serum transaminase levels (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]) who underwent abdominal computed tomographic (CT) scan for blunt abdominal trauma were reviewed. Nineteen patients (44.2%) had AST levels >450 IU/L and ALT levels >250 IU/L, and 17 of these 19 patients had hepatic injury identified on abdominal CT scan. Of the 43 patients, 25 (58.1%) had AST and ALT levels of less than 450 IU/L and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The increase of blood ALT is associated with a series of liver dysfunction problems including liver injury and infection of viral hepatitis. 23 In the present study, administration of INH with RIF significantly increased serum ALT and AST, whereas treatment of Dendrobine (100 and 200 mg/kg) significantly decreased serum ALT and AST, indicating Dendrobine possessed liver protective effects. Consistent with these results, we also observed that Dendrobine (100 and 200 mg/kg) ameliorated liver histopathological changes induced by INH and RIF.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The increase of blood ALT is associated with a series of liver dysfunction problems including liver injury and infection of viral hepatitis. 23 In the present study, administration of INH with RIF significantly increased serum ALT and AST, whereas treatment of Dendrobine (100 and 200 mg/kg) significantly decreased serum ALT and AST, indicating Dendrobine possessed liver protective effects. Consistent with these results, we also observed that Dendrobine (100 and 200 mg/kg) ameliorated liver histopathological changes induced by INH and RIF.…”
Section: Discussionsupporting
confidence: 49%
“…Both ALT and AST are commonly used markers for the evaluation of liver injury. 23,24 AST is responsible for the transferase of the amino group and is usually elevated due to liver dysfunction including liver cell infection or necrosis. 24 ALT is a transaminase enzyme widely used in the clinical examination for liver function tests.…”
Section: Discussionmentioning
confidence: 99%
“…There were no signi cant differences in sex, age, and clinical symptoms between the mild and moderate-severe groups. The ALT, AST, ALP, and GGT levels signi cantly correlated with the severity of liver injury, while the TBil level did not differ signi cantly between the two groups, suggesting that transaminase was a predictor of the severity of liver injury [20][21][22][23]17]. Furthermore, 97 cases had been exposed to more than one type of implicated drug for the primary disease before the liver injury occurred.…”
Section: Discussionmentioning
confidence: 96%
“…[ 18 ] In a study conducted among paediatric patients with BAT, none of them with normal hepatic transaminase levels had liver injury identifiable on computed tomography. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%